Internet of Things (IoT) Cloud Based Model for Low Cost Demand Side Management Infrastructure - Oyetola, O. K.; Okubanjo, A. A.; Okandeji, A. A.; Olaluwoye, O. O.; Alao, P. O.; Ukagu, S. N. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2019)
This paper presents a model for low cost demand side management infrastructure using cloud-based technology and internet of things to facilitate the implementation of smart grid in Nigeria. The electricity market has experienced a rapid increase in demand attributed to unprecedented growth in human population, urbanization, and industrialization. Accordingly, utilities are faced with the challenge of meeting daily energy demand. Research has shown that 45% of electricity generated are wasted or cannot be accounted for. Energy management is thus a major issue affecting the power sector of Nigeria. Efficient utilization of energy is therefore crucial for sustainable development both from an economic and ecological perspective. The proposed Smart, Low Cost and IoT-enabled power distribution board can be adopted and implemented as part of energy conservation measures to reduce energy demand in domestic building and mitigate the energy crisis in the country. With the IoT based smart board energy management, users can get personalized recommendation of actions for energy conservation and load shifting, and have control over the energy use and the billing system.